Black and latinx adolescents' developing understandings about poverty, inequality, and opportunity. Issue 2 (3rd April 2023) - Diaz, Brianna; May, Sidney; Seider, Scott
Abstract: This mixed-methods, longitudinal study utilized survey data from a sample of (primarily) Black and Latinx adolescents' ( n  = 643) and qualitative interviews with a subset of adolescents ( n  = 39) to consider changes in adolescents' beliefs about poverty and economic inequality throughout high school as well as the sources of their beliefs. Adolescents demonstrated significant, linear growth in their beliefs that poverty was caused by structural factors. This finding resonated with analyses of four waves of qualitative interviews in which a majority of participating adolescents shifted from citing individualistic causes to structural causes in their explanations of economic inequality and the opportunity structure in the United States. In explaining the sources of these beliefs, participating adolescents most frequently cited personal experiences, school-related experiences, and social media.